Relationships Between Academic Environment, Peer Relationship, Time Management And Psychological Well-Being - Hanina Halimatussaidiyah Hamsan (AL-FIKRA, 2017)
The purpose of this study was to determine the relationship between academic environment, peer relationship, time management and psychological well-being among final year students in Universiti Putra Malaysia. The study also determines the level of each stressor, and the relationship between each independent variable (academic environment, peer relationship, time management) and dependent variable (psychological well-being) among final year students. Besides, this study also Respondents were 333 final year students who study at Faculty of Human Ecology (FEM), Faculty of Economic and Management (FEP), and Faculty of Engineering (FK). They were selected based on Proportionate stratified random sampling. A self-administered questionnaire was used as a tool for data collection. University Environment Scale (Gloria and Karpius, 1996), Index of Peer Relationship (Walter W. Hudson, 1992), The Time Management Behavior Scale (Macan, 1990), and were used to measure academic environment, peer relationship, time management respectively. Dependent variable which was psychological well-being was measured by using Depression Anxiety Stress Scale 21 (DASS 21) which developed by Lovibond and Lovibond’s in year 1995. The results showed that majority of student had moderate level of perception to academic environment, setting goal and priorities, planning and scheduling, perceived control over time, preference for disorganization, overall time management behaviour and moderate level on depression. Besides, most of majority student have low peer relationship, extremely severe anxiety, and had normal stress. There is significant correlation between academic environment and depression (r=0.149**). Respectively, peer relationship was found have significant relationship with the psychological well-being subscales: depression (r=-0.468***), anxiety (r=0.374***), and stress (r=0.441***). Time management also have significant relationship between depression (r=-0.189***), anxiety (r=0.207***), and stress (r=0.197***). Academic environment have no significant relationship between anxiety (p>0.05) and stress (p>0.05). The study concluded that peer relationship (PR), and time management (TM) have significant predictor towards depression (ΒPR=0.458; ΒTM=0.233), anxiety (ΒPR =0.407; ΒTM =0.209), and stress (ΒPR=0.463; ΒTM=0.212) among final year students. Among the two predictors, peer relationship was found have most significant towards depression, anxiety, and stress of final year student, followed by time management. Study suggested that university should develop intention program, appropriate counselling service to student. Besides, student should learn good time management skills and habit in order to develop positive psychological well-being. Future study are encourage to include more possible sources of student psychological well-being, add more size of sample and apply different data collection tools for deeper investigation.